Tipos de familias en el proceso de adaptación escolar de los niños y niñas del centro de educación inicial Pío Jaramillo Alvarado de la ciudad de Loja. Período 2014 - Gonzalez Pardo, Wilma Irene (2015)
This thesis makes Re: TYPES OF FAMILIES IN THE PROCESS OF ADAPTATION SCHOOL OF THE BOYS AND GIRLS OF THE CENTRO DE EDUCACIÓN INICIAL PIO JARAMILLO ALVARADO FROM THE CITY OF LOJA. PERIOD 2014. The general objective which was formulated for research was: to investigate whether the types of family influence the process of adaptation school for the children of the Center of education initial Pio Jaramillo Alvarado from the city of Loja period 2014. For the development of the following research work included the following methods: Scientific, Inductive - duct Ivo, Synthetic analytical and statistic al the same which formed the basis for the method and reasoning of the characteristics and features presented in this investigation; the technique used was: the survey applied to master them to get to know the importance that has the family within the process of adaptation of children; and the test of evaluation of the intra-household relations (FF-SIL) which was aimed at parents of education initial Pio Jaramillo Alvarado Center family to know the type of family operation that surrounds the child. Of the results obtained with the application of psycho-pedagogical survey teachers was reached to conclude that: The family atmosphere is very important since it helps to promote the adaptation of the child, the family helps giving affection, security, trust and contributes to dialogue with him and explaining the new things you will experience at school. Family functioning was determined important as mood and psychological depend much attention that the child will during class and so will facilitate the pre-school learning. Within the affections and values perceived by the child at home are love, understanding and affection which are the main and very important to the child affection, respect, punctuality, responsibility, loyalty, commitment and other securities of the aforementioned also purchased at home which will help to a better performance in school life?